Le développement des droits miniers au Québec à la fin du XIXe siècle - Armstrong, Robert (L'Actualité économique)

(untitled) (HEC Montréal, 1983)
AbstractThis paper examines the forces at work in shaping the definition of mining rights in Quebec at the end of the 19th century. Using the Davis-North model of institutional change and some insights from the theory of rent-seeking, the author attempts to identify the origins of the provincial legal framework which has been in force since the turn of the century.